Kajian Sistem Manajemen Keselamatan dan Kesehatan Kerja (SMK3) pada Proyek Pembangunan Pabrik CPO Washing PT Multimas Nabati Asahan - Tasya Aulia; Betty Nopri Silitonga; Wirdatun Nafiah Putri (Universitas Methodist Indonesia, 2026)
Occupational Health and Safety (OHS) is a crucial aspect of construction, especially in projects such as the construction of the Crude Palm Oil (CPO) Washing plant at PT Multimas Nabati Asahan. The Occupational Health and Safety Management System (OHSMS) aims to prevent accidents and occupational diseases through the implementation of systematic policies, procedures, and supervision. This study aims to assess the implementation of OHSMS in the CPO Washing project at PT Multimas Nabati Asahan by identifying the level of compliance with OHS regulations, the effectiveness of safety procedures, and the factors influencing their implementation. The research method used is a combination of quantitative and qualitative approaches through field observations, analysis of data collected from questionnaires distributed to workers, and interviews conducted by the OHS personnel. The results indicate that although most of the OHSMS standards have been implemented in accordance with Government Regulation No. 50 of 2012 and Ministerial Regulation No. 10 of 2021, there are still several aspects that need improvement, particularly in safety training and field supervision. The main factors affecting the implementation of OHSMS include workers' awareness, budget constraints, and compliance with the applicable regulations.